Validity Of PALACA Media On Enumeration Material For Grade 4 Elementary School - Andayani, Sinta; Damayanti, Widya Anggun; Kristiyani, Leony; Taqwa, Aldino Khoirozadit; Ardianti, Sekar Dwi (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2025)
Introduction/Primary Objective: This study aims to describe the validation and practicality of PALACA (Numeric Board) media as a mathematics learning aid on the material of enumerated numbers for grade IV elementary school students. Research Methods : The media was developed using the Research and Development (R&D) method with a modified Borg and Gall model. Validation was conducted by media experts, material experts, and educational practitioners to assess the feasibility of using the media in learning. Findings/Results: The validation results show that PALACA media obtained an average score of 4.8 from media experts and practitioners, as well as 4.0 from material experts, which indicates that this media is very suitable for use. The results of the teacher's practicality test of the media reached 96.6% and the students' responses amounted to 95% which showed very good acceptance from direct users. PALACA media is considered to be able to increase students' motivation and understanding of the concept of counting numbers through a concrete and interactive approach. Conclusion : Thus, this media can be an effective alternative in learning mathematics in elementary schools. This research also contributes to the development of visual-based and participatory learning media. However, the trial was conducted on a limited scale so further research needs to be done with a larger sample to strengthen the generalization of the results.